Sociophonetics Analysis Of Youth Slang In Medan - Donna Ria Pasaribu; Tiara Kristina Pasaribu; Hotnida Irawaty Simanjuntak; Rachel Triarta Manurung; Gomos Damberk Sinaga (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study explores the sociophonetics characteristics of youth slang in Medan, Indonesia, focusing on its linguistic features, origins, and social functions. Employing a descriptive qualitative approach, the research investigates how slang is formed and used by teenagers which are gen z in Medan's urban communities. The analysis reveals that Medan slang is influenced by Malay, Hokkien, and Batak languages, alongside Indonesian and English, with unique phonetic shifts and word formation processes such as syllable alteration, abbreviations, and acronyms. The study also examines the types of slang using Allan and Budridge theory which are fresh and creative, flippant, imitative, acronym, and clipping. The data will be collected through questionnaires online. Then, some respondents will be interviewed so as to analyze the phonetic aspect of the slang. After the slang have been transcribed phonetically, they will be analyzed phonetically. By documenting the phonetic patterns and cultural significance of Medan slang, this research contributes to a broader understanding of language variation and change in multilingual urban settings.